Determination of fracture parameters of concrete based on water-cement ratio - Ince, Ragip; Alyamac, Kuerst Esat (Natl Inst Science Communication, 2008)
The aim of this Study is to predict formulas based on the Abrams' Law between fracture parameters of concrete and w/c. Therefore, a series of three-point bend test on specimens were performed. The beams were made from mixes with water/cement ratios varying in the range of 0.34-0.85. The fracture parameters for each mix were calculated according to a popular fracture mechanics approach two-parameter model. The present experimental data indicate that the fracture parameters of two-parameter model are inversely proportional to w/c ratios. In conclusion, the present test results are in agreement with the Abrams' Law.
Keywords: Process Zone Length; Prediction; Energy; Model